Identification of the Regulatory Elements and Target Genes of Megakaryopoietic Transcription Factor MEF2C - Kong, Xianguo; Ma, Lin; Chen, Edward; Shaw, Chad A.; Edelstein, Leonard C. (Thrombosis and Haemostasis, 2019)
Megakaryopoiesis produces specialized haematopoietic stem cells in the bone marrow that give rise to megakaryocytes which ultimately produce platelets. Defects in megakaryopoiesis can result in altered platelet counts and physiology, leading to dysfunctional haemostasis and thrombosis. Additionally, dysregulated megakaryopoiesis is also associated with myeloid pathologies. Transcription factors play critical roles in cell differentiation by regulating the temporal and spatial patterns of gene expression which ultimately decide cell fate. Several transcription factors have been described as regulating megakaryopoiesis including myocyte enhancer factor 2C (MEF2C); however, the genes regulated by MEF2C that influence megakaryopoiesis have not been reported. Using chromatin immunoprecipitation-sequencing and Gene Ontology data we identified five candidate genes that are bound by MEF2C and regulate megakaryopoiesis: MOV10, AGO3, HDAC1, RBBP5 and WASF2. To study expression of these genes, we silenced MEF2C gene expression in the Meg01 megakaryocytic cell line and in induced pluripotent stem cells by CRISPR/Cas9 editing. We also knocked down MEF2C expression in cord blood-derived haematopoietic stem cells by siRNA. We found that absent or reduced MEF2C expression resulted in defects in megakaryocytic differentiation and reduced levels of the candidate target genes. Luciferase assays confirmed that genomic sequences within the target genes are regulated by MEF2C levels. Finally, we demonstrate that small deletions linked to a platelet count-associated single nucleotide polymorphism alter transcriptional activity, suggesting a mechanism by which genetic variation in MEF2C alters platelet production. These data help elucidate the mechanism behind MEF2C regulation of megakaryopoiesis and genetic variation driving platelet production.
Keywords: MEF2C; megakaryopoiesis; megakaryocytes; haematopoiesis; transcription